Determinants of LV dP/dtmax and QRS duration with different fusion strategies in cardiac resynchronisation therapy. Issue 1 (7th May 2021) - Odland, Hans Henrik; Holm, Torbjørn; Gammelsrud, Lars Ove; Cornelussen, Richard; Kongsgaard, Erik
Abstract : Background: We designed this study to assess the acute effects of different fusion strategies and left ventricular (LV) pre-excitation/post-excitation on LV dP/dtmax and QRS duration (QRSd). Methods: We measured LV dP/dtmax and QRSd in 19 patients having cardiac resynchronisation therapy (CRT). Two groups of biventricular pacing were compared: pacing the left ventricle (LV) with FUSION with intrinsic right ventricle (RV) activation (FUSION), and pacing the LV and RV with NO FUSION with intrinsic RV activation. In the NO FUSION group, the RV was paced before the expected QRS onset. A quadripolar LV lead enabled distal, proximal and multipoint pacing (MPP). The LV was stimulated relative in time to either RV pace or QRS-onset in four pre-excitation/post-excitation classes (PCs). We analysed the interactions of two groups (FUSION/NO FUSION) with three different electrode configurations, each paced with four different degrees of LV pre-excitation (PC1–4) in a statistical model. Results: LV dP/dtmax was higher with NO FUSION than with FUSION (769±46 mm Hg/s vs 746±46 mm Hg/s, p<0.01), while there was no difference in QRSd (NO FUSION 156±2 ms and FUSION 155±2 ms). LV dP/dtmax and QRSd increased with LV pre-excitation compared with pacing timed to QRS/RV pace-onset regardless of electrode configuration. Overall, pacing LV close to QRS-onset (FUSION) with MPP shortened QRSd the most, while LV dP/dtmax increased the most with LV pre-excitation. Conclusion: We show how a beneficial change in QRSd dissociates from the haemodynamic change in LV dP/dtmax with different biventricular pacing strategies. In this study, LV pre-excitation was the main determinant of LV dP/dtmax, while QRSd shortens with optimal resynchronisation.